Serum levels of soluble st2 and their association with microparticles and disease activity in systemic lupus erythematosus (2020)
ABSTRACT: Background ST2 is an IL-33 receptor (a member of the IL-1 receptor family), existing in a transmembrane form (ST2L) and is also alternatively spliced to produce a secreted soluble form (sST2) and a membrane-anchored variant without the immunoglobulin-like motif (ST2V). High levels of sST2 have been reported in inflammatory diseases, including systemic lupus erythematosus (SLE). Additionally, higher levels of Microparticles (MPs) (small membrane vesicles) have been reported in SLE patients, being an important source of autoantigens and inflammatory mediators. Based on these considerations, our study aims to measure the serum levels of sST2 in SLE patients, examining their association with disease activity and steroid consumption. Additionally, we aim to propose that MPs are an important source of ST2. Methods Forty-six SLE patients were evaluated for disease activity (determined by SLEDAI), sST2 were measured by sandwich ELISA in serum samples and compared with 10 age- and sex-matched healthy controls (HCs). MPs were isolated from plasma from 9 SLE patients and 9 HC, and we evaluated the ST2 content in these vesicles by western blot. Results Serum sST2 level was significantly higher in active SLE patients compared with HCs (p<0.001), and in inactive patients compared with HCs (P<0.01). We demonstrated higher sST2 levels among SLE patients on steroid treatment, with MPs from SLE patients containing ST2. Conclusions We found elevated serum sST2 level in SLE patients, being higher in active patients; therefore ST2 could be an activity SLE biomarker. Additionally, MPs from SLE patients contain ST2, thus MPs could be an important source of circulating ST2, transporting and transferring ST2 to different cells for intercellular communication, consequently contributing to SLE pathogenesis.